Increasing Student Motivation in Informatics Through the Application of Quizziz Interactive Learning Media - Lutfia (PT. Global Research Collaboration, 2026)
Learning motivation is an important factor that influences students’ success in learning informatics, which requires both conceptual understanding and technical skills. This study aims to improve students’ learning motivation in informatics subjects through the implementation of interactive learning media. The research method employed was Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. Interactive learning media were applied as instructional actions to enhance student engagement. The results indicate a significant increase in students’ learning motivation from the first cycle to the second cycle, as evidenced by improvements in active participation, learning enthusiasm, task completion, and understanding of the material. The implementation of interactive learning media was proven to create a more engaging learning environment and encourage students’ active involvement in the learning process. Therefore, it can be concluded that interactive learning media are effective as a learning strategy to enhance students’ learning motivation in informatics subjects in the digital era.